Stress analysis of ceramic coatings under spherical indentation: Influence of a metallic interlayer - Quy, Le Minh; Thinh, Tran Ich (Vietnam Journal of Mechanics, 2006)
Spherical indentation problems of ceramic coatings/metallic interlayer/ductile substrate were investigated numerically by axisymmetric FEA for two typical ceramic coatings with relatively high and low elastic modulus deposited on aluminum alloy and carbon steel. Various indenter radius-coating thickness ratios and interlayer thickness-coating thickness ratios were used in the modeling. Radial stress distributions were discussed in connection with model parameters. The results showed that the suitable metallic interlayer could improve resistance of ceramic coating systems through reducing the peak tensile radial stress on the surface and interface of ceramic coatings.